Mobile Security Vehicle’s based on Internet of Things - Muchammad Husni; R. V. H. Ginardi; K. Gozali; R. Rahman; A. S. Indrawanti; M. I. Senoaji (Universitas Muhammadiyah Yogyakarta, 2021)
The purpose of this research is to design and build a mobile security vehicle based on the Internet of Things (IoT) that combines to Arduino-based microcontroller, internet networks, and the needed hardware. The design is intended to monitor and control the vehicle condition and monitor the vehicle location based on IoT. This research uses hardware and software components. The hardware uses the Arduino-based microcontroller that connects to some modules. This research uses Relay Module 2 Channel HL-525 to control the vehicle machine, GPS Module Neo-7M to get the vehicle location, SIM800L Module to connect to the internet network, and ACS-712 Voltage sensor to detect the voltage in the vehicle electricity. This research uses multi-platform (web application) as the component software to monitor and control the vehicle condition and its location. The result of this research is Mobile Security Vehicle’s System Based on Arduino where the system can satisfy some functional needs such as can monitoring motorcycle location, controlling alarm, and motorcycle electricity to avoid theft through a web application that can be used in multi-platform.